From infection to healing: The use of plant viruses in bioactive hydrogels. (16th July 2020) - Dickmeis, Christina; Kauth, Louisa; Commandeur, Ulrich
Abstract: Plant viruses show great diversity in shape and size, but each species forms unique nucleoprotein particles that are symmetrical and monodisperse. The genetically programed structure of plant viruses allows them to be modified by genetic engineering, bioconjugation, or encapsulation to form virus nanoparticles (VNPs) that are suitable for a broad range of applications. Plant VNPs can be used to present foreign proteins or epitopes, to construct inorganic hybrid materials, or to carry molecular cargos, allowing their utilization as imaging reagents, immunomodulators, therapeutics, nanoreactors, and biosensors. The medical applications of plant viruses benefit from their inability to infect and replicate in human cells. The structural properties of plant viruses also make them useful as components of hydrogels for tissue engineering. Hydrogels are three‐dimensional networks composed of hydrophilic polymers that can absorb large amounts of water. They are used as supports for tissue regeneration, as reservoirs for controlled drug release, and are found in contact lenses, many wound healing materials, and hygiene products. They are also useful in ecological applications such as wastewater treatment. Hydrogel‐based matrices are structurally similar to the native extracellular matrix (ECM) and provide a scaffold for the attachment of cells. To fully replicate the functions of the ECM it is necessary to augment hydrogels with biological cues that regulate cellular interactions. This can be achieved by incorporating functionalized VNPs displaying ligands that influence the mechanical characteristics of hydrogels and their biological properties, promoting the survival, proliferation, migration, and differentiation of embedded cells. This article is categorized under: Implantable Materials and Surgical Technologies > Nanomaterials and Implants Biology‐Inspired Nanomaterials > Protein and Virus‐Based Structures Implantable Materials and Surgical Technologies > Nanotechnology in Tissue Repair and Replacement Abstract : Plant virus nanoparticles are promising as hydrogel components for biomedical and personal care products as well as broader applications such as environmental remediation. Virus coat proteins can be engineered to display specific molecular cues for the bioactivation and functionalization of hydrogels, as well as influencing the mechanical behavior and stability of the hydrogel matrix.